Evaluation of Nurses’ Understanding of Compartment Syndrome - Hawraa Hussain Yousif; Mansi, Qusay Hasan; Mohamed Abbar Sharhan (International Journal of Research in Medical Surgical Nursing, 2026)
Background: When left untreated, compartment syndrome is a condition that causes permanent secondary muscular and nerve ischemia and characterised by excruciating pain brought on by elevated extracellular pressure found in the confined compartment of the calf musculature, which hinders local circulatory. Objective: This study's objective was to evaluate nurses' understanding of acute compartment syndrome. Techniques: Between October 2023 and March 2024, a descriptive study was conducted to determine nurses' understanding of compartment syndrome. The Arabic version of the created questionnaire was used for data collection. All of the respondents who were part of the study sample were asked similar questions using the same questionnaire. The Muhammad Al-Moussawi Hospital, Bint Al-Huda Hospital, and Al Azhar Hospital in Nasiriyah City served as the study's setting—a selected sample of 50 nurses. Results: The demographic features of the nurse sample are described in presented study. Age, gender, place of residence, and educational attainment are all included. Eighty percent of the sample is between the ages of twenty and twenty-nine; lesser proportion are between the ages of thirty and thirty-nine (18%) and forty and older (2%). A total of 50 nurses participated in the study. Overall knowledge levels were classified as poor (18%), moderate (52%), and good (30%). No statistically significant association was found between nurses’ knowledge and age or gender (p > 0.05). However, a statistically significant association was observed between knowledge level and residence (p = 0.009) as well as educational level (p = 0.013). It shows the frequency and percentage of nurses falling into each category. The table also shows no statistically significant association between total knowledge and questions. Conclusions: It shows the domains in which the nurses' knowledge is moderate. The relationship between nurses' expertise and their educational attainment is statistically significant.